Ancient Traditions of the Virgin Mary's Dormition and Assumption - Shoemaker, Stephen J. (Oxford University Press, 2023)
The ancient Dormition and Assumption traditions, a remarkably diverse collection of narratives recounting the end of the Virgin Mary's life, first emerge into historical view from an uncertain past during the fifth and sixth centuries. Initially appearing in Syria, Palestine, and Egypt, these legends spread rapidly throughout the Christian world, resulting in over 60 different narratives from before the tenth century preserved in nine ancient languages. This study presents a detailed analysis of the earliest traditions of Mary's death, including the evidence of the earliest Marian liturgical traditions and related archaeological evidence as well as the numerous narrative sources. Most of the early narratives belong to one of several distinctive literary families, whose members bear evidence of close textual relations. Many previous scholars have attempted to arrange the different narrative types in a developmental typology, according to which the story of Mary's death was transformed to reflect various developments in early Christian Mariology. Nevertheless, evidence to support these theories is wanting, and the present state of our knowledge suggests that the narrative diversity of the early Dormition traditions arose from several independent ‘origins’ rather than through ordered evolution from a single original type. Likewise, scholars have often asserted a connection between the origin of the Dormition traditions and resistance to the council of Chalcedon, but the traditions themselves make this an extremely unlikely proposal. While most of the traditions cannot be dated much before the fifth century, a few of the narratives were almost certainly in composed by the third century, if not even earlier. These narratives in particular bear evidence of contact with gnostic Christianity. Several of the most important narratives are translated in appendices, most appearing in English for the first time.